Eletrodos Quimicamente Modificados com compostos de Cobalto coloidal como sensor eletroquímico de Hidroquinona, Glicose e Lapachol - STADNIK, ANDRÉIA (2016)
The preparation, characterization and electrochemical behavior of films containing cobalt were studied aiming to explore their electrocatalytic properties, because is important electroactive material. In this study the oxyhydroxide of cobalt [CoO(OH).Acetate and CoO(OH).NO3] were obtained from two precursors: acetate and nitrate of cobalt, respectively, for analysis and comparison of the interference of precursors ions, in the obtained materials. The structural and morphological, and composition characterizations were made by use of these techniques: Simultaneous Thermal Analysis (TGA-DTA), Molecular Spectroscopy (FTIR), Electronic Spectroscopy (UV-Vis), Scanning Electron Microscopy and Energy Dispersive Spectroscopy (SEM - EDS) and X Ray Diffraction (XRD). In the electrochemical study the colloids served of chemical modifier of the electrode [EQM_CoO(OH).Acetate and EQM_CoO(OH).NO3], using as a substrate the platinum (Pt). In this stage, the cyclic voltammetry technique (CV) was used to establish parameters, as sweep speed, concentration, mass transport process, among others. Studies of possible applications as sensors of Glucose (Gli) and Hydroquinone (HQ) at low concentrations were realized. Lastly, of so increasing the efficiency of CoO(OH), this was intercalated in the lamellae of Laponite clay (Lap) by a simple and direct route, in the getting of the Lap_CoO(OH). This mixed material was characterized as for the chemical, morphological, structural and electrochemical composition (with the use of Au and Pt substrates) and applied as an electrochemical of Lapachol (Lapol) sensor.